Dynamic capabilities and financial behavior to accelerate MSME performance recovery and its impacts on business sustainability - Supramono Supramono; Theresia Woro Damayanti; Dhian Adhitya (Journal of Innovation and Entrepreneurship)
Abstract The purpose of this study is to investigate the impact of dynamic capabilities and financial behavior on the speed of performance recovery for micro, small, and medium enterprises (MSMEs), as well as the impact of dynamic capabilities, financial behavior, and speed of MSME performance recovery on business sustainability. The data were collected from a total of 450 food and beverage MSMEs in Central Java, Indonesia, through field surveys. Then, the data were analyzed using partial least squares-structural equation modeling (PLS-SEM). The results revealed the importance of dynamic capabilities and financial behavior to accelerate MSME performance recovery after the COVID-19 pandemic. Additionally, this study found that the dynamic capabilities, financial behavior, and speed of performance recovery are determinants of business sustainability. These findings highlight the importance of MSME actors in continuing to monitor the dynamics of their environment and respond to them with products and services that meet the demands in order to achieve long-term sustainability of MSME performance.